Uma Proposta de Rede Social Espontânea para Interação Ubíqua em Eventos - dos Santos, Marcelo da Silva; da Costa, Cristiano André; Barbosa, Jorge Luis Victoria (Proceedings of Brazilian Symposium on Ubiquitous and Pervasive Computing (SBCUP), 2016)
The popularization of mobile devices and the increasing spread of social networks has fostered the development of applications in order to manage and encourage interactions through their devices. This article presents a model of spontaneous social network to foster the interaction of participants in events such as conferences and congresses. In addition to presenting the model, called Mingle, we show the prototype created for experimentation. The assessment followed two visions, the first focusing on access statistics to the environment and the second checking usability, effectiveness, efficiency and user satisfaction. Results showed good reception Mingle and potential for implementation on a larger scale.